Literature Review on Tools & Applications of Data Mining - Shrivastava, Anshu; Jain, Jay Kumar; Chauhan, Dipti (International Journal of Computer Sciences and Engineering, 2023)
There are many new disciplines that have emerged as a result of technological advancement. Every day, enormous amounts of data are produced in many different areas, including science, engineering, health, and business. Data mining is a technique for gathering data from various sources and organizing it to produce insightful conclusions. Companies’ today look to stay ahead of the competition by making it a priority to keep up with all new developments in data science and analytics. This paper explains data mining`s applications in various areas as well as its methods and tools. This study concentrated on different data mining tools that are beneficial and identified as key fields of data mining technology. We are aware of the numerous domestic and international businesses, as well as small and big organizations.